Comparison of eight prehospital stroke scales to detect intracranial large-vessel occlusion in suspected stroke (PRESTO): a prospective observational study. Issue 3 (March 2021) - Duvekot, Martijne H C; Venema, Esmee; Rozeman, Anouk D; Moudrous, Walid; Vermeij, Frédérique H; Biekart, Marileen; Lingsma, Hester F; Maasland, Lisette; Wijnhoud, Annemarie D; Mulder, Laus J M M; Alblas, Kees C L; van Eijkelenburg, Roeland P J; et al.
Summary: Background: Due to the time-sensitive effect of endovascular treatment, rapid prehospital identification of large-vessel occlusion in individuals with suspected stroke is essential to optimise outcome. Interhospital transfers are an important cause of delay of endovascular treatment. Prehospital stroke scales have been proposed to select patients with large-vessel occlusion for direct transport to an endovascular-capable intervention centre. We aimed to prospectively validate eight prehospital stroke scales in the field. Methods: We did a multicentre, prospective, observational cohort study of adults with suspected stroke (aged ≥18 years) who were transported by ambulance to one of eight hospitals in southwest Netherlands. Suspected stroke was defined by a positive Face-Arm-Speech-Time (FAST) test. We included individuals with blood glucose of at least 2·5 mmol/L. People who presented more than 6 h after symptom onset were excluded from the analysis. After structured training, paramedics used a mobile app to assess items from eight prehospital stroke scales: Rapid Arterial oCclusion Evaluation (RACE), Los Angeles Motor Scale (LAMS), Cincinnati Stroke Triage Assessment Tool (C-STAT), Gaze-Face-Arm-Speech-Time (G-FAST), Prehospital Acute Stroke Severity (PASS), Cincinnati Prehospital Stroke Scale (CPSS), Conveniently-Grasped Field Assessment Stroke Triage (CG-FAST), and the FAST-PLUS (Face-Arm-Speech-Time plus severe arm or leg motor deficit) test. The primary outcome was the clinical diagnosis of ischaemic stroke with a proximal intracranial large-vessel occlusion in the anterior circulation (aLVO) on CT angiography. Baseline neuroimaging was centrally assessed by neuroradiologists to validate the true occlusion status. Prehospital stroke scale performance was expressed as the area under the receiver operating characteristic curve (AUC) and was compared with National Institutes of Health Stroke Scale (NIHSS) scores assessed by clinicians at the emergency department. This study was registered at the Netherlands Trial Register, NL7387. Findings: Between Aug 13, 2018, and Sept 2, 2019, 1039 people (median age 72 years [IQR 61–81]) with suspected stroke were identified by paramedics, of whom 120 (12%) were diagnosed with aLVO. Of all prehospital stroke scales, the AUC for RACE was highest (0·83, 95% CI 0·79–0·86), followed by the AUC for G-FAST (0·80, 0·76–0·84), CG-FAST (0·80, 0·76–0·84), LAMS (0·79, 0·75–0·83), CPSS (0·79, 0·75–0·83), PASS (0·76, 0·72–0·80), C-STAT (0·75, 0·71–0·80), and FAST-PLUS (0·72, 0·67–0·76). The NIHSS as assessed by a clinician in the emergency department did somewhat better than the prehospital stroke scales with an AUC of 0·86 (95% CI 0·83–0·89). Interpretation: Prehospital stroke scales detect aLVO with acceptable-to-good accuracy. RACE, G-FAST, and CG-FAST are the best performing prehospital stroke scales out of the eight scales tested and approach the performance of the clinician-assessed NIHSS. Further studies are needed to investigate whether use of these scales in regional transportation strategies can optimise outcomes of patients with ischaemic stroke. Funding: BeterKeten Collaboration and Theia Foundation (Zilveren Kruis).